Aspek Hukum Pembiayaan Ijarah dan IMBT Antara Fikih dan PenerapanPerbankan - Muhamad, Mar’ie; Fitri, Nurul Amalia; Masse, Rahman Ambo; Sapa, Nasrullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the legal aspects of the Ijarah and Ijarah Muntahiyah Bit Tamlik (IMBT) contracts, two commonly used instruments in asset-based Islamic financing. The Ijarah contract refers to a lease agreement for the use of goods or services in exchange for a specified payment, while IMBT is an extended form of Ijarah that concludes with the transfer of asset ownership to the lessee at the end of the lease term. The objective of this research is to analyze the conformity of these contracts with Islamic legal principles (fiqh muamalah) and their implementation within Indonesia’s positive legal framework, including regulations issued by the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This study employs a normative-juridical approach by analyzing fatwas, statutory regulations, and case studies on the application of Ijarah and IMBT contracts in Islamic financial institutions. The findings reveal that although both contracts have gained legitimacy under Sharia and national law, challenges remain in their practical implementation, regulatory supervision, and legal certainty. The study recommends enhanced awareness of Islamic legal principles, regulatory harmonization, and strengthened oversight mechanisms in the execution of Ijarah and IMBT contracts.